2003
DOI: 10.4315/0362-028x-66.4.559
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Listeria monocytogenes in Ready-to-Eat Foods

Abstract: The purpose of this study was to develop data on the risk of listeriosis to support a science-based strategy for addressing Listeria monocytogenes in foods in the United States. Eight categories of ready-to-eat foods were collected over 14 to 23 months from retail markets at Maryland and northern California FoodNet sites. The product categories included luncheon meats, deli salads, fresh soft "Hispanic-style" cheeses, bagged salads, blue-veined and soft mold-ripened cheeses, smoked seafood, and seafood salads.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
251
2
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(272 citation statements)
references
References 22 publications
10
251
2
9
Order By: Relevance
“…Although a cheese from another producer was contaminated at retail by a strain with the outbreak-associated PFGE type, this was probably a result of cross-contamination since no positive samples were detected in the processing plant. Increased risk of cross-contamination of ready-to-eat foods by L. monocytogenes in a retail environment has been demonstrated in several studies [17][18][19][20]. For example, a quantitative risk assessment conducted by Endrikat et al suggested that ready-toeat deli meats sliced at a retailer are five times more likely to cause listeriosis than pre-packaged products (per annum basis) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although a cheese from another producer was contaminated at retail by a strain with the outbreak-associated PFGE type, this was probably a result of cross-contamination since no positive samples were detected in the processing plant. Increased risk of cross-contamination of ready-to-eat foods by L. monocytogenes in a retail environment has been demonstrated in several studies [17][18][19][20]. For example, a quantitative risk assessment conducted by Endrikat et al suggested that ready-toeat deli meats sliced at a retailer are five times more likely to cause listeriosis than pre-packaged products (per annum basis) [21].…”
Section: Discussionmentioning
confidence: 99%
“…FSIS and others have found, however, that the risks associated with retail-sliced deli meats to be five times higher than for prepackaged deli meats (gombas et al 2003(gombas et al , Endrikat et al 2010. The ranking of Listeria in dairy products (5th) is driven by a number of outbreaks associated with soft ripened cheeses made from unpasteurized milk, particularly queso fresco, a traditional fresh cheese common in mexican cuisine (voetsch et al 2007).…”
Section: By Pathogenmentioning
confidence: 99%
“…While there have been significant gains over the last decade in reducing contamination rates of pre-sliced, packaged deli meats (USDA 2010), numerous studies have found that retail-sliced deli meats have significantly higher prevalence and levels of Listeria monocytogenes (gombas et al 2003(gombas et al , Endrikat et al 2010. FSIS scientists estimate that risks from retail-sliced deli meats are nearly five times higher than prepackaged equivalents, and responsible for 70 percent of the deaths due to the category (Endrikat et al 2010).…”
Section: Qaly Loss Cost Of Illnessmentioning
confidence: 99%
“…It is believed that 5 percent of the general population may be asymptomatic carriers of Listeria, but the percentage may be higher in particular groups, such as slaughterhouse workers. (Gombas et al, 2003). This research is important because the prevalence in the food supply does not match the rate of illness in the population, and because the outcome of illness in susceptible individuals is very severe.…”
Section: Background On Challenges To the Zero Tolerance Initiativementioning
confidence: 99%